2007
DOI: 10.1007/s10620-007-9838-9
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type 1 Receptor Expression in Human Gastric Cancer and Induces MMP2 and MMP9 Expression in MKN-28 Cells

Abstract: Angiotensin II (Ang II), a main effector peptide in the renin-angiotensin system, acts as a growth-promoting and angiogenic factor via angiotensin II receptor1 (AT1R). In this study, we investigated the expression of angiotensin II type1 receptor (AT1R) in gastric cancer and the effects of Ang II on the expression of MMP2 and MMP9 in the human gastric cancer cell line MKN-28 cells. The expression of the Ang II type I receptor was examined by western and immunocytochemistry in gastric cancer cell lines and dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 18 publications
4
26
0
Order By: Relevance
“…Previous cancer studies have demonstrated that AngII augments the migration and invasion of choriocarcinoma cells through the AT1R and induces MMP-2 and MMP-9 expression in gastric cancer cells (25)(26)(27). Consistent with these effects of AngII, we showed that treatment with AngII significantly increases the invasive ability of A549 lung cancer cells.…”
Section: Discussionsupporting
confidence: 89%
“…Previous cancer studies have demonstrated that AngII augments the migration and invasion of choriocarcinoma cells through the AT1R and induces MMP-2 and MMP-9 expression in gastric cancer cells (25)(26)(27). Consistent with these effects of AngII, we showed that treatment with AngII significantly increases the invasive ability of A549 lung cancer cells.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding histologic localization of the AT1 receptor, immunoreactivity was evident in membranous and cytoplasmic patterns. This is in accordance with findings described by Huang et al (18).…”
Section: At1 Expression In Human Gastric Cancer Cell Lines and Tissuessupporting
confidence: 94%
“…This study also showed AT1 receptor protein was overexpressed immnohistochemically in pancreatic ductal cancer cells, whereas the colon cancer cells had extremely weak or negative immunoreactivity for AT1 receptor (7). In gastric caner, it has been also reported that AT1 receptor is overexpressed in cancer tissues (18)(19)(20)(21), little information exists on the local synthesis of angiotensin II. Classically, the physiological activity of angiotensin II has long been recognized to be dependent on conversion of its precursor angiotensin I by angiotensin-converting enzyme (ACE).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Members of the MMP family, in particular, MMP-9, are associated with regulation of cancer cell invasion and metastasis, the most insidious and life-threating aspects of cancer (21,22). Therefore, the development of compounds capable of inhibiting MMP-9 could prove invaluable in the treatment of breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%